Pengaruh kampung KB pada intervensi gizi sensitif stunting di Desa Janegara - Setyawati, Vilda Ana Veria; Ramadha, Faizzatun (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2020)
Background: Stunting in Brebes, Central Java is the highest 100 in Indonesia. Through the Family Plan Village (Kampung KB), National Population and Family Planning Board (BKKBN) was given the mandate to contribute in accelerating the improvement of nutrition, especially the problem of stunting. 15,873 villages in Indonesia were formed as Kampung KB. However, there were no studies that describe the extent to which the program was effective.Objectives: This study aims to determine the effectiveness of the Kampung KB on sensitive intervention to prevent stunting.Methods: Experimental research with and one group only post test study design used. In 60 mothers of children under the age of 24 months starting in March-October 2019 in Janegara Village, Brebes Regency. The intervention carried out was the Kampung KB. Its activities at the study site are conducted from March-October 2019 in the study population's parents. The intervention was family counseling by family planning counselors (PKB). The variables measured included planning for household life, habituation of clean and healthy lifestyles in the family, empowering family at home, and responsive care. Data was collected using a questionnaire that was prepared independently and has been tested for validity and reliability. Analysis of the data used to prove the hypothesis is one sample t test.Results: Most of the mothers understand family life planning (75%), PHBS practices are appropriate (61.37%), the role of fathers is good (83.3%), and mothers have taken responsive care responsive care (55%). Kampung KB is effective for improving the practice of PHBS (p = 0.003) and the role of fathers in the family (p = 0.0001).Conclusion: Kampung KB was effective to increase (PHBS) and the role of fathers in parenting.Â